Relationship between structure and functional properties of starch from different cassava (Manihot esculenta Crantz) and yam (Dioscorea opposita Thunb) cultivars used for food and industrial processing. (1st January 2023) - Zou, Jinhao; Li, Yan; Wang, Feng; Su, Xiaojun; Li, Qingming
Abstract: This work investigated the functional properties of four varieties of yam starch and four varieties of cassava starch to better understand the relationship between the structure and properties of various forms of starch. The relationship between the functional properties and structure of starch was explored using Pearson correlation (PCs) and principal component analysis (PCA). The analyses demonstrated that yam starch and cassava starch differ significantly in structure and functional properties. Yam starches have a higher requirement during gelatinization, may hold a higher trough viscosity and final viscosity, and are easier to retrograde after gelatinization; this results in starch gels with a higher hardness and gel strength. While the cassava starches have a higher breakdown, their starch gels are fluid and squishy. The differences in starch functional properties were linked to particle size, short-range ordered structure, protein content, and average radius of gyration in PCs and PCA. The present investigation demonstrates a link between the functional properties of cassava and yam starch and their structural features and suggests that acceptable processing methods and applications for these tuber starches be selected based on their functional properties. Highlights: The structure and functional properties of cassava and yam starch were compared. Yam starch gel has high hardness and gel strength. Cassava starch gel has strong fluidity, high softness and high ductility. There was a significant correlation between the structure and functional properties of starch.